Factors that contribute to academic stress among students in northern Malaysia higher learning institution / Nur Basirah Zahari ... [et al.] - Zahari, Nur Basirah; Lazim, Kalsom; Andin Salamat, Azni Syafena (2021)
Academic stress can be defined as the product of a combination of academic requirements that exceed the adaptive resources available to the individual (Phillips, Halder & Hasib, 2019). Abouserie (1994); Aherne (2001); Sadri and Marcoulides (1997) as cited from Poon & Lee (2012) claimed that academic stress can be triggered by tests and subsequent waiting for results, financial pressures, shifts in eating and sleeping habits, heavy workloads, adaptation to community and ethnic disparities, language incompetence, lack of support from family and friends. However, the situation was different for university students, as people always assumed that academic stress is an unusual issue among the population of university students, since the only thing that university students were expected to do was study and study, which was never seen as a stressful task (Reddy, Menon & Thattil, 2018). In today's reality, the educational system is a very stressful experience and during academic activities, students face a great deal of academic stress (Kuruppuarachchi, Manpreet & Maheshwar, 2012) as cited from (Manap, Hamid & Ghani, 2019).